Implikasi Hukum Lingkungan Terhadap Industri Pertambangan Bangka - Rasta Buana, Syahfa Rizi; Desra, Iskara; Alayya, Siti Balqis; Marela, Karintan; Agustin, Kevia Dela (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
Mining has become one of the main sectors in economic growth, especially in Indonesia with a significant contribution to Gross Domestic Product and state income. Bangka is one of the largest tin producers in Indonesia, but mining activities have caused significant environmental damage. Legislation such as Law Number 32 of 2009 concerning environmental protection and management requires the mining industry to comply with environmental standards in their operations. This regulation covers aspects such as licensing, waste management, conservation of natural resources, and the application of sanctions for violations. The government is trying to enforce these regulations through various policies and supervision, but still faces challenges in implementing and enforcing the law. This research shows that environmental legal regulations influence mining practices in Bangka, with significant implications for the environment and community welfare.